Monitoring and Evaluation of Tree Seedling Planting as an Effort to Improve Food Security - Endang Suprapti; Suroto Suroto; Novia Susanti (Asosiasi Dosen Muda Indonesia, 2026)
Climate change and environmental degradation have become significant challenges affecting environmental sustainability and long-term food security. Tree planting programs have been widely implemented as an environmental conservation strategy; however, empirical evaluations of their implementation and effectiveness remain limited. This study aims to evaluate the implementation of a tree seedling planting program conducted through collaboration between the Ministry of Environment and Forestry and three higher education institutions in Indonesia. A Convergent Parallel Mixed Methods approach was employed by integrating quantitative and qualitative data collected through field observations, interviews, documentation, and administrative records. Quantitative analysis assessed planting performance based on the number of seedlings distributed, planted, and surviving, while qualitative analysis explored program implementation and monitoring processes. The findings indicate that all administrative requirements and planting procedures were successfully fulfilled. A total of 12,000 tree seedlings were distributed and planted across three locations, with a 100% survival rate recorded during the monitoring period. Field observations confirmed that geotagging documentation, monitoring activities, and institutional collaboration contributed significantly to program accountability and implementation success. The study concludes that systematic monitoring and evaluation strengthen environmental conservation programs by ensuring planting compliance and supporting environmental sustainability and food security. The findings provide practical implications for improving monitoring mechanisms in future community-based environmental conservation initiatives.